Lexical Collocations Ascertained in the Descriptive Writings of the English Students - Rachmawati, Rachmawati; Al arif, Tubagus Zam Zam (International Journal of Language Teaching and Education, 2023)
The current research depicts the points as pursue: 1) to portray the types of lexical collocations ascertained in the descriptive writings of the English Education students, 2) to represent the types of colloquial errors depicted in the descriptive writings of the English Education students, and 3) to descsribe the English Education students’ difficulties in allocating the lexicons in their descriptive writings. The present study has drawn on a descriptive-interpretative qualitative design on the linguistic behaviors (lexicons) and writing skill of the research subjects holistically on the bases of the contexts of the writings that have been previously offered. The data of the current study have been analyzed by means of the interactive model. This interactive model consists of three research pathways: data reduction, data display, and conclusion/ data verification that are integrated before, being and after the data are collected. Within this model, the entire data are not reviewed (reduced): the data reduction has been carried out in several ways, for instance by selecting the descriptive writings allied to the topic of this study, i.e., colloquial lexicons. Commencing the 8 available types of colloquial lexicons, 3 (three) lexicons are not countered by the research participants, to be precise: substitution, conjunction, and exclamation. Correspondingly, these colloquial lexicons are encoded by the research participants’ native (Indonesian) language intervention, lack of vocabulary, word-for-word translation and direct translation, ignorance of the rules on Indonesian and English, and lack of knowledge about the nature of collocations.